Birdman - Hayder, Mo (Hayder, Mo. Jack Caffery thriller, 1999)
In Greenwich, England, Inspector Jack Caffery investigates the case of a woman with a live bird sewn in her body. The case is the latest in a series of murders of women whose bodies were surgically mutilated. A debut in fiction by a British woman.